Irish and Polish in a New Context of Diversity in Northern Ireland’s Schools - Mckendry, Eugene (Studia Celtica Posnaniensia, 2017)
While Modern Languages are in decline generally in the United Kingdom’s post-primary schools, including in Northern Ireland (Speak to the Future 2014), the international focus on primary languages has reawakened interest in the curricular area, even after the ending in 2015 of the Northern Ireland Primary Modern Languages Programme which promoted Spanish, Irish and Polish in primary schools. This paper will consider the situation in policy and practice of Modern Languages education, and Irish in particular, in Northern Ireland’s schools. During the years of economic growth in the 1990s Ireland, North and South, changed from being a country of net emigration to be an attractive country to immigrants, only to revert to large-scale emigration with the post-2008 economic downturn. While schools in Great Britain have had a long experience of receiving pupils from diverse ethnic and linguistic backgrounds, firstly from the British Empire and Commonwealth countries, Northern Ireland did not attract many such pupils due to its weaker economic condition and the conflict of the Northern Ireland Troubles. The influx from Poland and other Accession Countries following the expansion of the European Union in 2004 led to a sudden, significant increase in non-English speaking Newcomer pupils (DENI 2017). The discussion in Northern Ireland about a diverse democracy has hitherto concentrated on the historical religious and political divide, where Unionist antipathy led to the Irish Language being dubbed the ‘Green Litmus Test’ of Community Relations (Cultural Traditions Group 1994). Nevertheless, the increasing diversity can hopefully ‘have a leavening effect on a society that has long been frozen in its “two traditions” divide’ (OFMDFM 2005a: 10). This paper will revisit the role and potential of Irish within the curricular areas of Cultural Heritage and Citizenship. An argument will also be made for the importance of language awareness, interculturalism and transferable language learning skills in Northern Ireland’s expanded linguistic environment with a particular focus on Polish.